A Short Survey of Yemeni Sufism from Its Inception up to the Thirteenth Century - Muhammad Aziz (International Institute of Islamic Thought, 2009)
This paper analyzes the historical conditions of Yemen’s Sufi movement from the beginning of Islam up to the rise of the Rasulid dynasty in the thirteenth century. This is a very difficult task, given the lack of adequate sources and sufficient academic attention in both the East and theWest. Certainly, a few sentences about the subject can be found scattered in Sufi literature at large, but a respectable study of the period’s mysticism can hardly be found.1 Thus, I will focus on the major authorities who first contributed to the ascetic movement’s development, discuss why a major decline of intellectual activities occurred in many metropolises, and if the existing ascetic conditions were transformed into mystical tendencies during the ninth century due to the alleged impact ofDhu’n-Nun al-Misri (d. 860). This is followed by a brief discussion ofwhat contributed to the revival of the country’s intellectual and economic activities. After that, I will attempt to portray the status of the major ascetics and prominent mystics credited with spreading and diffusing the so-called Islamic saintly miracles (karamat). The trademark of both ascetics and mystics across the centuries, this feature became more prevalent fromthe beginning of the twelfth century onward. I will conclude with a brief note on the most three celebrated figures of Yemen’s religious and cultural history: Abu al-Ghayth ibn Jamil (d. 1253) and his rival Ahmad ibn `Alwan (d. 1266) from the mountainous area, andMuhammad ibn `Ali al-`Alawi, known as al-Faqih al-Muqaddam (d. 1256), from Hadramawt.